Bird diversity in a protected area in the Atlantic Forest-Pampas ecotone of coastal Rio Grande do Sul State, southern Brazil - João Paulo Gava Just; Ricardo Dossa Colvero; Jairo José Zocche (Acta Biológica Catarinense, 2022)
The subtropical coastal ecosystems of Brazil are located in the ecotone between the Atlantic Forest (MA) and the Pampas. The delimitation of biogeographic boundaries is still debated. In order to improve the understanding of these limits, the diversity of birds in the MA-Pampa ecotone in the Environmental Protection Area (APA) of Lagoa de Itapeva, Rio Grande do Sul, Brazil, and its surroundings was evaluated. A list of APA birds was generated and the occurrence of endemic, threatened and migratory species discussed. A total of 162 species were recorded during the APA surveys and another 38 species in the immediate surroundings, totaling 200 species. The local avifauna has few endangered and endemic species, but the presence of multiple habitats allows the occurrence of a diverse community of wetlands, restingas, fields and lowland forests. In terms of biogeographic affinities, MA and Pampa endemic species present in the studied ecotone are few, widely distributed and common, with MA endemics dominating. Long-term monitoring of bird assemblages is recommended, using point counting and mist net capture[1]recapture protocols, considering native habitats separately, in order to assist in APA management, as birds are highly sensitive to environmental change.